Fabrication of Planar Microelectrode Array Using Laser-Patterned ITO and SU-8 - Hee Soo Jeong (MDPI AG, 2021)
For several decades, microelectrode array (MEA) has been a powerful tool for in vitro neural electrophysiology because it provides a unique approach for monitoring the activity of a number of neurons over time. Due to the various applications of MEAs with different types of cells and tissues, there is an increasing need to customize the electrode designs. However, the fabrication of conventional MEAs requires several microfabrication procedures of deposition, etching, and photolithography. In this study, we proposed a simple fabrication method with a laser-patterned indium tin oxide (ITO) conductor and SU-8 photoresist insulation. Unlike in a conventional metal patterning process, only the outlines of ITO conductors are ablated by laser without removing background ITO. Insulation is achieved simply via SU-8 photolithography. The electrode sites are electroplated with iridium oxide (IrOX) to improve the electrochemical properties. The fabricated MEAs are electrochemically characterized and the stability of insulation is also confirmed by impedance monitoring for three weeks. Dissociated neurons of rat hippocampi are cultured on MEAs to verify the biocompatibility and the capacity for extracellular neural recording. The electrochemical and electrophysiological results with the fabricated MEAs are similar to those from conventional SiNX-insulated MEAs. Therefore, the proposed MEA with laser-patterned ITO and SU-8 is cost-effective and equivalently feasible compared with the conventional MEAs fabricated using thin-film microfabrication techniques.